Translating Jewish Poland into Canadian Yiddish: Symcha Petrushka’s Mishnayes - Margolis, Rebecca (TTR, 2009)
In 1945, with European Jewry in ruins, Polish-born Symcha Petrushka published the first of six volumes of his Yiddish translation and interpretation of the Mishna. Produced in Petrushka’s adopted home in Montreal, the Mishnayes was conceived as a work of popularization to render one of the core texts of the Jewish tradition accessible to the Jewish masses in their common vernacular, and on the eve of World War II Yiddish was the lingua franca of millions of Jews in Europe as well as worldwide. However, in the aftermath of the Holocaust and the destruction of the locus of Yiddish civilization and millions of speakers combined with acculturation away from Yiddish in Jewish population centres in North America, Petrushka’s Mishnayes remains a tribute to the vanished world of Polish Jewry.